Haematological and immunological reference intervals for adult population in the state of Amhara, Ethiopia. Issue 7 (30th May 2018) - Enawgaw, Bamlaku; Birhan, Wubet; Abebe, Molla; Terefe, Betelihem; Baynes, Habtamu Wondifraw; Deressa, Tekalign; Melku, Mulugeta
Abstract: Objective: Reference intervals (RIs) currently being used in Ethiopia are derived from western populations. Thus, this study aimed to establish locally derived haematological and immunological RIs. Method: The study was conducted in Amhara State, Ethiopia with a total of 967 (55.2% males) participants. 56.9% of males and 43.1% of females were eligible for haematological and immunological RI determination. A non‐parametric test was used for the determination of upper (97.5th percentile) and lower (2.5th percentile) reference interval limits with 95% CI. The Harris and Boyd Rule was used to determine the need of partitioning of reference intervals based on gender. Result: The established 95% reference intervals (2.5th–97.5th percentile) were: for WBC: 3–11.2 × 10 9 /l; for platelet: 90–399 × 10 9 /l; for RBC: 4–6 × 10 12 /l for males and 3.5–5.6 × 10 12 /l for females; for haemoglobin: (Hgb) 12–18.9 g/dl for males and 10.7–17.5 g/dl for females; for PCV: 35.7–55.3% for males and 32.2–50.1% for females; for CD4: 400–1430 × 10 9 /l for males and 466–1523 × 10 9 /l for females; for CD4 percentage: 18–49.1% for males and 21.3–52.9% for females; for MCV: 81–100 fl; for MCH: 25.3–34.6 pg; MCHC: 28.8–36.9%; for RDW: 11.6–15.4% and for MPV: 8–12.3 fl. Males had significantly higher RBC, Hgb and PCV than females. CD4 counts and CD4 percentage were significantly higher in females. Conclusion: The reference intervals established in this study differ from others and thus should be used for the interpretation of laboratory results in diagnosis and safety monitoring in clinical trials in Amhara.